Dragon's teeth : tales from North Kosovo - Bancroft, Ian (Balkan politics and society., 2020)
Ian Bancroft provides an original ethnographic account of north Kosovo, mixing firsthand interviews and anecdotes with historical background and academic insight. The book goes to the heart of the border and boundary regions and mixed areas on the periphery to tell the stories of those caught up on the front lines of conflict.